The Representation of Masculinity in Postmodern British Literature: the Case of Ian McEwan’s Enduring Love (1997) - Abdellaoui, Ahlem; Bederina, Sarah Ahlam (Faculty of Letters and Foreign Languages Department of English, 2023)
By the late twentieth century, masculinity studies have evolved to become a major multidisciplinary field. Today, much of masculinity studies seem to be concentrating on the analysis of cinematic and literary representations of masculinity. In this light, the study at hand sought to critically examine the portrayal of masculinity in postmodern fiction, namely in Enduring Love (1997) by the British writer Ian Russell McEwan. The descriptive approach, as well as the analytical approach, were used to conduct this study. The former helped to establish conceptual and theoretical foundations for the study, while the latter helped find adequate answers to certain queries and issues by examining the social, cultural and psychological contexts in Enduring Love. The analysis was based on major contributions to men‘s studies by the most prominent figures from the field like Raewyn Connell and Judith Butler, in addition to other masculinity critics. From psychology, Freud‘s theory of ―the Uncanny‖ was of paramount importance. The study ultimately revealed that masculinity is transitory, flexible and questionable. It is constructed within particular socio-cultural and historical contexts and changes according to the circumstances within which it resides. It also signified the crucial role of the individual‘s psychological state in the construction, deconstruction and alteration of the masculine identity. It is, thus, highly recommended to emphasize the psychological elements when examining literary masculinities, to further widen the interpretations.